2020
DOI: 10.1007/s12144-020-00838-6
|View full text |Cite
|
Sign up to set email alerts
|

Decision to forgive scale and emotional forgiveness scale in a polish sample

Abstract: The paper presents the concept of emotional and decisional forgiveness proposed by Worthington et al. (Journal of Behavioral Medicine, 30, 291-302, 2007) and employing the Polish versions of the Decision to Forgive Scale and Emotional Forgiveness Scale developed in line with this theory. Both scales are tools measuring episodic forgiveness is forgiveness for a specific transgression that is made once. Decisional forgiveness is a declaration to forgive, whereas emotional forgiveness is a "change of heart". The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…The Polish adaptation of the Emotional Forgiveness Scale (EFS; Hook et al, 2012; Mróz et al, 2020) was used to measure the level of emotional forgiveness of a particular offense. The scale consists of eight items and two subscales assessing the presence of positive emotions (PP) and reduction of negative feelings toward the transgressor (RN).…”
Section: Methodsmentioning
confidence: 99%
“…The Polish adaptation of the Emotional Forgiveness Scale (EFS; Hook et al, 2012; Mróz et al, 2020) was used to measure the level of emotional forgiveness of a particular offense. The scale consists of eight items and two subscales assessing the presence of positive emotions (PP) and reduction of negative feelings toward the transgressor (RN).…”
Section: Methodsmentioning
confidence: 99%
“…These findings largely diverge from prior work that suggests both decisional and emotional forgiveness tend to be related to lower distress (e.g., Kurniati et al, 2017 ; Cowden et al, 2019a ), although mixed evidence has been documented. For example, Mróz et al (2022) found that certain indicators of distress were uncorrelated with either one (e.g., depression symptoms) or both (e.g., negative affect) interpersonal forgiveness processes. Our findings could be explained by the one-month lag between assessments, as more time might be needed to find evidence of associations between each interpersonal forgiveness process and the indicators of distress that were examined.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this theorizing, existing evidence generally suggests that emotional forgiveness tends to have stronger negative associations with indicators of distress (e.g., depression symptoms, stress) and stronger positive associations with different indicators of well-being (e.g., relationship satisfaction, gratitude) compared to decisional forgiveness (e.g., Chi et al, 2019;Cowden et al, 2019a;Wu et al, 2022). However, not all evidence is consistent with this picture, as some studies have reported stronger correlations with some indicators of distress (e.g., depression symptoms; Mróz et al, 2022) and well-being (e.g., perceived posttraumatic growth; Byra et al, 2022) for decisional forgiveness rather than emotional forgiveness. These findings suggest that emotional forgiveness may not always perform a dominant function in lowering distress and improving well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Forgiveness Scale (Kaleta, Mróz, Guzewicz, 2016) or Toussaint's Forgiveness Scale (Charzyńska, Heszen, 2013), no instrument measuring state (self)forgiveness available in Polish -TRIM (Kossakowska, Kwiatek (2017), as well as EFS and DTFS (Mróz, Kaleta, Sołtys, 2020) offers such subscales. Therefore, it was concluded that adaptation of the scale measuring state self-forgiveness will enable development of research on forgiveness in the Polish population.…”
Section: Page 384mentioning
confidence: 99%